Time-related changes in the knowledge of HIV/AIDS among followers of various religions in India [version 2; peer review: 2 approved] - Amna Khalid; Rizwan Qaisar; Asima Karim; M. Azhar Hussain; Firdos Ahmad (F1000Research, 2023)
Background The public knowledge levels about Human Immunodeficiency-Virus/Acquired Immunodeficiency Syndrome (HIV/AIDS) have been assessed in previous studies; however, time-related trends in association with socio-demographic standards among the followers of major religions in India are not known. Objectives We assessed the 2005-06, 2015-16, and 2019-21 demographic and health survey (DHS) data from India to investigate trends in the levels of knowledge of HIV/AIDS among Hindus, Muslims, and Christians in relation to standard socio-demographic variables over a period of 16 years. Methods The age range of the population was 15-54 years (n=611,821). The HIV/AIDS-related knowledge was assessed by developing a composite index based on ten questions about several aspects of HIV/AIDS, such as the mode of spread. We applied Chi-square and Kruskal-Wallis tests to investigate whether people had heard about HIV/AIDS and their overall HIV knowledge in relation to several socio-demographic standards. Results Generally, a higher increase in knowledge level was found between the first and second DHS surveys (2006-2016) as compared to between the second and third DHS surveys (2016-2021). We found the highest increase in the level of HIV/AIDS knowledge among Christian women followed by Hindus, whereas Muslims had the least increase over 16 years. Being a female, uneducated, poor, previously married, or having rural residence were associated with the highest increase in the knowledge of HIV/AIDS. Conclusion Christian women had the highest increase in HIV/AIDS-related knowledge then came Christian men and followers of other religions. We also found the highest increase in HIV/AIDS-related knowledge among the poorest, uneducated, and rural residents. Our findings may help formulate public health strategies targeting various less knowledgeable groups to reduce the incidence of HIV/AIDS.